1998
DOI: 10.1046/j.0909-8836.1998.eos106501.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucosal changes in coeliac patients on a gluten‐free diet

Abstract: Oral mucosal lesions or dental enamel defects may be the only presenting features of coeliac disease. A series of 128 patients with coeliac disease (CD) on a gluten-free diet (GFD), 8 patients with a newly diagnosed CD, and 30 healthy controls participated in a clinical and histopathological study of their oral mucosa. Oral mucosal lesions occurred in 71/128 GFD-treated CD patients. in 4/8 untreated and in 10/30 controls, and oral symptoms in 85/128, in 6/8 and in 10/30, respectively. Five CD patients had apht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 0 publications
5
55
0
6
Order By: Relevance
“…According to Campisi et al, these changes may appear in the form of small multiple changes, or in the form of single larger aphtha [7]. Malnutrition is reported as a presumable cause of those changes, especially iron, folic acid and vitamin B12 deficiencies which are very frequent in patients who do not adhere to gluten free diet [12,33]. This thesis seems to be confirmed by the studies of Bucci et al and Campisi, who observed an improvement in the condition of the oral mucosa after the introduction of a strict gluten free diet [7,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Campisi et al, these changes may appear in the form of small multiple changes, or in the form of single larger aphtha [7]. Malnutrition is reported as a presumable cause of those changes, especially iron, folic acid and vitamin B12 deficiencies which are very frequent in patients who do not adhere to gluten free diet [12,33]. This thesis seems to be confirmed by the studies of Bucci et al and Campisi, who observed an improvement in the condition of the oral mucosa after the introduction of a strict gluten free diet [7,18].…”
mentioning
confidence: 99%
“…However, attention should be paid to a possible link between aphthae and gluten intolerance, which is widespread in the human population, but frequently undiagnosed [3,21]. Apart from RAS, in patients with celiac disease other disturbances of oral mucosa such as ulceration, erythema, atrophic glossitis and subjective symptoms: pain and a burning sensation (particularly of the tongue) and dryness, were observed [7,33]. However, Lähteenoja et al did not note a strict dependence of gluten-free diet, and subsiding of the complaints [33].…”
mentioning
confidence: 99%
“…Dental enamel defects in permanent and mucosal inflammatory lesions such as recurrent aphthous ulcers and angular cheilitis are common in CD (17)(18)(19). Moreover, dental caries due to the decreased salivary flow can be seen frequently in SS.…”
Section: Discussionmentioning
confidence: 99%
“…In atypical pattern, digestive symptoms are not sharply expressed, and it is characterized by symptoms such as thyroid dysfunction, epilepsy, short stature, iron deficiency anemia refractory to iron replacement, infertility, constipation and herpetiformis dermatitis [12]. Despite these various possible symptoms, Lahteenoja et al [13] stated that the oral mucosal lesions or tooth enamel defects may be the only signs present in this pattern. In the silent pattern, patients are asymptomatic or mildly symptomatic, but they have positive serology, and exhibit changes in intestinal mucosa.…”
Section: Clinical Featuresmentioning
confidence: 99%